Experimental and numerical investigation of phase material as heat storage from a concentrating solar collector - Hagos, Ftwi Yohaness; Azmi, W. H.; Mamat, Rizalman; Abdullah, Abdul Adam; Aziz, Amir; Oumer, Ahmed Nurye (2017)
Using the solar energy in day time has no problem. For night time however, the system needs some kind of back-up system to make the daytime solar energy available. This back-up should have high-density energy storage and constant working temperature to perform a specific application. Latent heat storage using phase change materials (PCM) is one way of storing thermal energy. In the current study, a latent heat storage that uses a PCM material is used to store the solar energy aimed at utilizing solar energy for cooking. The PCM is a mixture of 60% NaNO3 and 40% KNO3 that are known as solar salts. The storage has a welded parallel aluminum fins with a gap of 40 mm in between to enhance the thermal conductivity during the charging-discharging process of the storage. The fins are extruded outside of the storage container to enable a side charging technique for the PCM. A prototype was developed with a solar salt of 17.5 kg and is tested for charging-discharging. The numerical simulation done on ANSYS and experimental results show an agreement and the system registered a 41.6% efficiency.